2012
DOI: 10.1200/jop.2011.000478
|View full text |Cite
|
Sign up to set email alerts
|

Power of an Effective Clinical Conversation: Improving Accrual Onto Clinical Trials

Abstract: The National Cancer Institute (NCI) is actively transforming clinical trials to revitalize the clinical trials system and improve patient accrual. For more than 30 years, NCI has provided information and communication resources about cancer clinical trials. The Institute supports a clinical trials Web site (www.cancer.gov/clinicaltrials) that receives nearly a half million page views a month. In addition, NCI's Cancer Information Service (800-4-CANCER, chat and e-mail) responds to 1,750 clinical trial inquirie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…A portion of this information is consistent with the recommendations provided by the literature on clinical trials accrual [5,9,54]. However, the choice of topics differed across the trainings, and not all key areas were reported as having been covered.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A portion of this information is consistent with the recommendations provided by the literature on clinical trials accrual [5,9,54]. However, the choice of topics differed across the trainings, and not all key areas were reported as having been covered.…”
Section: Discussionsupporting
confidence: 68%
“…Research on the reasons for clinical trials' low accrual rates has identified several key barriers, which include a low rate of physicians' referral [7,8]. Many physicians characterize discussions about research and clinical trials with patients as particularly challenging, a problem, which is rarely addressed, even by academic medical centers committed to the research enterprise [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐provider conversations are often the crucial moment when a patient decides whether to participate in a study (Parreco et al . ). Developing a best practices guide may be helpful to avoid these common barriers to recruitment in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, slow enrollment in clinical studies may also lead to a delay in the availability of new therapies and, therefore, slow the advancement of medical progress [2]. For example, a year delay in access to Herceptin would represent a total loss of $8 billion dollars of benefit for breast cancer patients in the United States [3]. Development of reliable and practical tools for accrual prediction is critical in clinical trials.…”
Section: Introductionmentioning
confidence: 99%